An Analysis of Requirement Engineering and Techniques: A Literature Review - Zakaria, Fariz; Utami, Ema (Universitas Komputer Indonesia, 2024)
This research explores the essentiality of software requirements engineering in cycles software development. The focus lies on three main techniques, namely Functional Requirement, Non-Functional Requirement, Viewpoint Orientation Requirement Definition (VORD), and analysis through USECASE (Use Case Diagram and Use Case Scenario). Through a review systematic literature, ten relevant articles have been comprehensively reviewed in order to understand these techniques. The research results show that functional and non-functional needs have a role central to software development. Functional requirements describe what is should be carried out by the system, while non-functional requirements include aspects such as performance and security aspects. The VORD approach is proven to be efficient in understanding various angles views involved in system requirements, through the steps of identification, structure, documentation, and system point of view mapping. Besides that, the USECASE method helps describe user interactions with the internal system real-world situations, providing deep insight into user needs. This research make significant contributions to understanding the nature of software requirements engineering, and provide an important foundation for future research and practice